7+3d-5=-1+2-12+d

Simple and best practice solution for 7+3d-5=-1+2-12+d equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3d-5=-1+2-12+d equation:


Simplifying
7 + 3d + -5 = -1 + 2 + -12 + d

Reorder the terms:
7 + -5 + 3d = -1 + 2 + -12 + d

Combine like terms: 7 + -5 = 2
2 + 3d = -1 + 2 + -12 + d

Combine like terms: -1 + 2 = 1
2 + 3d = 1 + -12 + d

Combine like terms: 1 + -12 = -11
2 + 3d = -11 + d

Solving
2 + 3d = -11 + d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-1d' to each side of the equation.
2 + 3d + -1d = -11 + d + -1d

Combine like terms: 3d + -1d = 2d
2 + 2d = -11 + d + -1d

Combine like terms: d + -1d = 0
2 + 2d = -11 + 0
2 + 2d = -11

Add '-2' to each side of the equation.
2 + -2 + 2d = -11 + -2

Combine like terms: 2 + -2 = 0
0 + 2d = -11 + -2
2d = -11 + -2

Combine like terms: -11 + -2 = -13
2d = -13

Divide each side by '2'.
d = -6.5

Simplifying
d = -6.5

See similar equations:

| 7+6x=4(x-5)+7 | | 2k^2-19k+10=0 | | 4t-t-5=2t-8 | | 15.4+3.5=-1.2h-6 | | 8(3b+3)=5b+5 | | 7s+2s-7s=8 | | -9x-6=4x+33 | | (5y+3)(2y+7)=11y-10 | | x^7-3x^6=0 | | Q+10=25 | | 4x-(9x+3)=7x-27 | | 4(c+1)=16 | | 6Z-5=37 | | .79x+230=43777 | | 16=80 | | 3x+15-6x=-(-x+1) | | [k-10]=30 | | 2(x-1)(x-5)=0 | | 16=480 | | 1.5d+5.25=3+2.25d | | 2x+35+5x-22= | | 0=-5+2x | | r-7.3=-7.1 | | 5n^2-4n-12=0 | | 2x+35-5x-22= | | -3X-24-5=9x+18+1 | | 9(3x+12)=10(2x+15) | | (3x-4)-(5x-3)= | | 20x+6x-2= | | r-7.9=7.5 | | 3+x=22-2 | | 6x-2=20x |

Equations solver categories